JCGP-Injective Rings With Some Types of Rings - Abdul-Jabbar, Abdullah M. (Sulaimani Journal for Pure and Applied Sciences, 2015)
The concept of right P-injective rings, which was first introduced by Ming in 1974. As a generalization of right P-injective rings, the notion of right JCP-injective rings, which was first introduced by Junchao in 2009. Now, in the present paper we introduce the notion of right JCGP-injective rings, which is stronger than right GP-injective rings due to Ming in 1985. Some properties, characterizations and main results for right JCGPinjective rings will be finding.
Keywords: JCPinjective rings; JCGPinjective rings; GPinjective rings; regular rings